Taxpayer Perceptions of Ease of Use, Digital Literacy, and Coretax System Quality in Fulfilling Tax Obligations at KPP Pratama Jember - Sahrido Sahrido; Debi Aurelia Azizah Kedua; Ari Fahimatussyam Putra Nusantara (The Future of Education Journal, 2026)
This research examines taxpayers’ perspectives regarding perceived ease of use, digital competence, and the quality of the Coretax system in carrying out tax responsibilities at KPP Pratama Jember amid the ongoing transformation of digital taxation. The study was driven by the growth in the number of registered taxpayers that was not followed by a balanced increase in annual tax return compliance, reflecting that the application of digital tax services has not entirely succeeded in improving taxpayer adherence. This research applied a descriptive qualitative method to gain a deeper understanding of taxpayers’ experiences and viewpoints toward the implementation of Coretax. Data collection was conducted through in-depth interviews, participatory observations, and documentation involving individual taxpayers, MSME taxpayers, and Account Representatives selected through purposive sampling techniques. The analysis process adopted the interactive model developed by Miles, Huberman, and Saldana, consisting of data reduction, data display, and conclusion formulation. The results indicate that taxpayers continue to encounter obstacles in adjusting from the previous system to Coretax, especially in comprehending reporting mechanisms and operating system features. Digital literacy emerged as a significant element affecting taxpayers’ capability to independently access digital tax facilities. Furthermore, various technical constraints, including mobile display issues, complicated navigation, and system disruptions during annual tax return submission, contributed to reduced user satisfaction and confidence in the system. The study concludes that the effectiveness of digital tax transformation is influenced not merely by technological infrastructure, but also by user preparedness, digital literacy, system reliability, and sustainable tax education initiatives.